The relationship between microclimate factors and fruit quality in different tree canopies of Xiahui No. 8 peach trees - Zhen, Junquan; Wang, Yuke; Xia, Hening; Li, Hui; Wu, Haixia; Zhao, Caiping; Wang, Dong (Frontiers in Plant Science, 2025)
In this study, 6-year-old Xiahui No. 8 peach trees were used to investigate the effects of microclimates on their fruit quality between open-center and Y-shaped tree canopies. The impacts of the two canopy structures on light distribution, temperature, and relative humidity (RH) within the canopy, and their correlation with fruit quality metrics such as weight, hardness, soluble solid content (SSC), and dry matter content (DMC) were analyzed. The open-center-shaped trees had more favorable light distribution, with higher light intensity in the upper canopy layers and a larger light interception area, leading to improved fruit yield and quality compared to Y-shaped trees. The open-center-shaped trees also had higher single fruit weight, percentage of large fruits, SSC, flesh DMC and fruit hardness. However, free acidity showed only a minor difference between the two tree shapes. The study also found significant differences in the fruit coloration across canopy layers, with fruits in the upper layers exhibiting better coloration and higher SSC. Light intensity ranged from 30–90% and was strongly and positively correlated with fruit quality, thereby influencing the fruit size, coloration, and sugar-acid ratio. Overall, the open-center-shaped trees prove to be more conducive to improving fruit quality and yield. Nevertheless, proper management of the tree shapes, branch distribution, and light intensity is essential in optimizing fruit quality and maximizing the economic benefits of peach orchards.